Variable-density solute transport in unconfined coastal aquifers with a subsurface dam - Fan, Yu; Shen, Chengji; Xie, Yifan; Lu, Chunhui; Zhang, Chenming; Li, Ling (Frontiers in Marine Science, 2024)
Recently, the influence of human engineering (e.g., subsurface dams) on solute transport in coastal aquifers has gradually become a hot topic. Although many studies have gained certain insights, the combined effects of subsurface dam and tides on variable-density solute transport remain unclear. Therefore, this study numerically investigated how a subsurface dam would affect variable-density solute transport, by constructing a 2-D conceptual model of the coastal aquifer. The results show that a subsurface dam blocks a portion of the solute plume, which can only be discharged by dilution at the edges, thereby altering its discharge pattern and reducing their discharge rate (Reduced by 15% in this study); the addition of a subsurface dam may either prolong or shorten the residence time of solute, primarily depending on the location rather than the height of the subsurface dam. In particular, a more landward subsurface dam would significantly increase the residence time; sensitivity analysis demonstrates that both the landward shift and the height increase of the subsurface dam contribute to a heightened ratio of dynamic mass distribution for the solute plume within the freshwater and saltwater zones of the aquifer, with maximum changes in mass distribution ratios of 87.22% and 300%, respectively. In addition, these factors cause the solute to migrate both seaward and landward, respectively, across the primary outflow regions of the aquiferocean interface. Results from this study may provide theoretical guidance for the optimal design and environmental impact assessment of subsurface dams.